HUBUNGAN KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA SELURUH BAGIAN DIVISI PT. PLN (PERSERO) AREA BEKASI - 1, Aprisani; Tobing, Josephine; Anggraini, Nenny (Universitas Kristen Indonesia, 2017)
Labor is one of the important factors that should be considered by the company in order to achieve objectives. Therefore in this case the company is required to manage resources in a planned manner. The research was conducted at PT. PLN (Persero) Area Bekasi to determine the relationship of emotional intelligence and motivation on employee performance. The purpose of this study was to determine the relationship of emotional intelligence and employee performance, labor relations and employee motivation, as well as the relationship of emotional intelligence and motivation to work with employees performance in PT. PLN (Persero) Area Bekasi. This research is descriptive-correlation with a sample of 44 employees and the data were analyzed using Spearman Rank analysis and correlation. The results of this study indicate that (1) there is a significant relationship between emotional intelligence and employee performance PT. PLN (Persero) Area Bekasi. This is indicated by the obtained t (6.572) is greater than t table (2.018). (2) there is a significant relationship between motivation and performance of employees of PT. PLN (Persero) Area Bekasi. This is indicated by the obtained t (6.045) is greater than t table (2.018). (3) there is a significant relationship between emotional intelligence and motivation on employee performance PT. PLN (Persero) Area Bekasi. This is indicated by the acquired Fhitung (41.765) is greater than F table (3,226). Based on the results, it can be concluded that the variables are strong and be positive. But from the descriptive respondents by filling the questionnaire indicators were rated the lowest.Keywords: motivation, performance, emotional intelligence